Cell death and disease (NPG, Macmillan Publishers, 2010)
Cell death & disease is a peer-reviewed open access online journal that publishes full-length papers, reviews and commentaries describing original research in the field of translational cell death. The journal seeks to encompass the breath of translational implications of cell death, and topics of particular concentration will include experimental medicine, cancer, immunity, internal medicine, and neuroscience.